POPULATION ASSESSMENT OF TARICAYA (Podocnemis unifilis) AND TEPARO (Phrynops geoffroanus) IN THE PURUS COMMUNAL RESERVE, UCAYALI, PERU - FLORES-PONCE, Frank Christian (2023)
The Yellow-spotted river turtle (Podocnemis unifilis) and the Geoffroy's side-necked turtle (Phrynops geoffroanus) represent species with high environmental and economic value. To assess the status of their populations, the abundance index (AI) was estimated through 20 aquatic transects of 10 km in length in three sectors: Alto Purús National Park (PNAP), Purús Communal Reserve (RCP) and Buffer Zone (communal territory adjacent to the RCP). 737 records were obtained with 2335 individuals sighted for Yellow-spotted river turtle (taricaya) and only 17 records with 25 individuals sighted for Geoffroy's side-necked turtle (teparo). The AI of the taricaya for CPR was 3.9 ind/km traveled (SE = 0.6). A greater AI could be evidenced in the subsectors within the PNAP and progressively lower AI in the sectors of the Buffer Zone (ZA) of the RCP. These results value the importance of protected natural areas (PNA) to maintain populations of species such as the taricaya; and represent the beginning of robust monitoring so that in the following seasons and together with other economic and social indicators, we have a general vision of the conservation status of the species in the RCP. In the case of the teparo species, although it is possible to make calculations of the abundance index, these do not have a biological interpretation of the population of the species in the RCP. It is up to the Head of the RCP to make adjustment decisions in the information gathering methods and/or sampling design for the evaluation of this important species.